2001
DOI: 10.1074/jbc.m105934200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificities of Recombinant Mannan-binding Lectin-associated Serine Proteases-1 and -2

Abstract: Mannan-binding lectin (MBL)-associated serine proteases-1 and 2 (MASP-1 and MASP-2) are homologous modular proteases that each interact with MBL, an oligomeric serum lectin involved in innate immunity. To precisely determine their substrate specificity, human MASP-1 and MASP-2, and fragments from their catalytic regions were expressed using a baculovirus/insect cells system. Recombinant MASP-2 displayed a rather wide, C1s-like esterolytic activity, and specifically cleaved complement proteins C2 and C4, with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
139
1
11

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 44 publications
(35 reference statements)
5
139
1
11
Order By: Relevance
“…Based on the crystal structure of the CUB1-EGF-CUB2 region of human MASP-2, Feinberg et al proposed a model in which a MASP-2 dimer was shown to easily dock inside a MBL dimer with the serine protease domain of MASP-2 near the flexible ␣-helical neck joint (15). Kinetic studies have shown that although C1s and MASP-2 have comparable C2-cleaving activities, MASP-2 is more efficient than C1s in cleaving C4 due to a 26-fold lower K m for the substrate (K m ϭ 0.074 M and 1.92 M, respectively) (18). Thus even though the stoichiometry of the MBL⅐MASP-2 complex of the lectin pathway might be similar to that reported for the C1 complex of the classical pathway in which one C1q hexamer binds to one C1s dimer (34,59), the reports suggest that the lectin pathway is more efficient than the classical pathway in cleaving C4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the crystal structure of the CUB1-EGF-CUB2 region of human MASP-2, Feinberg et al proposed a model in which a MASP-2 dimer was shown to easily dock inside a MBL dimer with the serine protease domain of MASP-2 near the flexible ␣-helical neck joint (15). Kinetic studies have shown that although C1s and MASP-2 have comparable C2-cleaving activities, MASP-2 is more efficient than C1s in cleaving C4 due to a 26-fold lower K m for the substrate (K m ϭ 0.074 M and 1.92 M, respectively) (18). Thus even though the stoichiometry of the MBL⅐MASP-2 complex of the lectin pathway might be similar to that reported for the C1 complex of the classical pathway in which one C1q hexamer binds to one C1s dimer (34,59), the reports suggest that the lectin pathway is more efficient than the classical pathway in cleaving C4.…”
Section: Discussionmentioning
confidence: 99%
“…Cleavage of C4 and C2 are mediated by C1s in the C1r 2 -C1s 2 tetramer, which gets activated upon the binding of C1 to antigen-antibody complexes (33,34). Similarly, cleavage of C4 and C2 upon activation of the lectin pathway is mediated by MASP-2 in the M1 complex (13,(17)(18)(19)35). Each type of MASP has been reported to form a homodimer (10,36,37), but the stoichiometry of MASPs in association with MBL has yet to be established.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MBL circulates in association with four structurally related proteins, the MBL-associated serine proteases (MASP)-1, -2, and -3 (10 -12) and a truncated form of MASP-2 called MAp19 (19-kDa MBL-associated protein) or small MBL-associated protein (13,14). Although the precise roles of the different complexes have not yet been elucidated, it is clear that the MBL-MASP-2 complex is sufficient to trigger complement activation through cleavage of C4 and C2 (15)(16)(17).…”
mentioning
confidence: 99%